Masyarakat Adat Dalam Konsepsi Hak Asasi Manusia Di Indonesia Yang Stagnan - Waluyo, Bambang Dwi (Interdependence Journal of International Studies, 2023)
The issue of indigenous peoples is becoming an endlessly vital issue in human rights. The rights of indigenous peoples still cannot be accommodated through national policy or international policies. Therefore, this paper identifies the reasons of problems regarding indigenous peoples still cannot be resolved even though there is UNDRIP (United Nations Declaration on the Rights of Indigenous Peoples). Coming out with the question "Why are the problems regarding the rights of indigenous peoples in Indonesia still unresolved", this paper pursues to discover the problems of indigenous peoples in Indonesia through a postcolonial perspective. With applying postcolonial theory, it can be seen that in matters of community rights, Indonesia enforces land management structures, domesticates the mind, and integrates their national economy with indigenous peoples, it results blurring of boundaries between customary and state territories.